The role of some biological and natural feed additives against the deleterious effect of diazinon in Nile tilapia (Oreochromis niloticus) - Hemat A. Abd El-Salam; Gamal A. Abdel-Rahman; Hemat K. Mahmoud; Tamer Ahmed Ismail; Mahmoud Alagawany (Aquaculture Reports)
The present research amid to investigate the toxic effect of diazinon (DZN) and assess the modulatory role of chitosan nanoparticle (ChNP), orange peel extract (OPE), spirulina platensis (SP) and curcumin nanoparticles (CNP) as feed additives in O. niloticus fish. A total of 900 fish were divided into six equal groups, each with 3 replicates by random distribution. The 1st group was kept as the control group which was fed a basal diet. The 2nd group (DZN) was given a basic diet and exposed to 1/10th of the 96-hour LC50 of DZN. The 3rd group (DZN+ChNP) was exposed to DZN (0.28 mg/L) + 1 gm ChNP/kg diet. The 4th group (DZN+OPE) was exposed to DZN (0.28 mg/L) + 2 gm OPE/kg diet. The 5th group (DZN+SP) was exposed to DZN (0.28 mg/L) + 5 gm SP/kg diet, while, the 6th group (DZN+SP) was exposed to DZN (0.28 mg/L) + 150 mg CNP/kg diet. Apart from feed conversion, DZN decreased fish's growth performance parameters as compared to the control, while these values were modulated with ChNP, SP or CNP supplement to fish with DZN exposure. Fish exposed to DZN had the lowest values Hb, RBCs WBCs, total protein, albumin and globulin and the highest values of ALT, AST and uric acid while dietary supplementation with ChNP, OPE, SP and CNP to DZN exposed fish restored their levels to the control values. Fish group fed diet supplemented with DZN+OPE or DZN+ChNP recorded the lowest value of ALT among all studied groups. DZN altered the lipid profile of exposed fish while the DZN+SP group had the best values of all lipid profile among all groups followed by DZN+CNP group. Fish exposed to DZN had lower serum lysozyme activity, immunoglobulin (M, A and G) levels and antioxidant parameters (SOD, GSH, CAT and TAC) while dietary supplementation of ChNP or OPE to DZN exposed fish had higher values for these traits but still under control values. The highest level of lipid peroxidation marker malondialdehyde (MDA) was observed in DZN group while dietary supplementation of ChNP or OPE to DZN exposed fish decreased the MDA level. According to the genetic distance and dendrogram for the analysis of genetic diversity between treatments, compared to control; it is clear that the highest genetic diversity was found with DZN group samples (4.80) while dietary treatments with ChNP, OPE or SP to DZN exposed fish showed the lowest diversity of (3.00, 3.32 and 3.87), respectively. It could be concluded that long-term exposure to a sub-lethal DZN dose resulted in growth retardation, haemato-biochemical alteration, immune depression, oxidative stress and genetic material damage of Nile tilapia. Furthermore, the antioxidant and protective properties of ChNP, OPE, SP, and CNP induced nearly total protection in fish exposed to DZN through diet.